Frequency of Hypothyroidism among Patients with Chronic Kidney Disease at a Tertiary Care Hospital in Pakistan: Frequency of Hypothyroidism among Patients with Chronic Kidney Disease - Ahmed, Anees; Ullah, Hamid; Hussain, Manzoor; Ali, Amjad; Ali, Murad; Shehzad, Shahid; Israr, Hamza; Amin, Ansa; Ali, Asim (Pakistan Journal of Health Sciences, 2026)
Patients with Chronic kidney disease (CKD) suffer from endocrine axis disruption as a part of the complications involving several other organ systems. Hypothyroidism is one of the imbalances seen in patients with CKD, both in clinical practice and research. Thyroid dysfunction remains undiagnosed due to its non-specific symptoms and lack of routine screening, especially in resource-limited settings. Objectives: To determine the frequency of hypothyroidism among patients with CKD and to differentiate its clinical and subclinical forms. Methods: This cross-sectional (descriptive) study was conducted over a period of six months in the Department of Medicine, Mardan Medical Complex, Khyber Pakhtunkhwa. 131 CKD patients (18-70 years) were recruited by non-probability consecutive sampling. Serum levels of thyroid-stimulating hormone (TSH), free T3, and free T4 were used to evaluate the patient’s thyroid status. Based on serum hormone levels, the patients were categorized into hypothyroidism, subclinical hypothyroidism, or euthyroid states. The data were analysed through SPSS (version 26.0). Results: Out of 131 CKD patients, clinical hypothyroidism was found in 24 (18.3%), while 27 (20.6%) of the patients had subclinical hypothyroidism. Thyroid dysfunction was more common in patients above 60 (p=0.003) and females (p=0.041). A significant association was also found with dialysis status (p=0.006). Conclusions: Hypothyroidism is a prevalent complication in CKD, especially among older and female patients. The study emphasizes the value of routine thyroid screening in all stages of CKD to facilitate early diagnosis and treatment, especially in dialysis-dependent people.